MENGURAI MAKNA CIVIL RELIGION PANCASILA SEBAGAI MORAL PUBLIK INDONESIA - Arief Firdaus (Cross-border, 2021)
Civil Religion terminology which was popularized by Robert N Bellah, a sociologist from the United States through his writing "Civil Religion in America" (1967), combines religious morals and moral goodness outside religion to become public morals. Civil religion is a minimum agreement regarding religious values that are held together, regardless of any religious beliefs held by each person or group. Individually, each is free to adhere to the teachings of his or her religion, but collectively all adhere to the beliefs agreed upon in the civil religion as fellow citizens of the nation. Civil Religion is not 'religion' (religion) in a general and ordinary sense (in the traditional sense), but civil religion is an agreement that social, state or political life must be accounted for before a conscience filled with religion. The conception of a civil religion in Indonesia is contained in Pancasila which is the meeting point where all colors and differences unite, the fulcrum which is the basis of law, as well as the point where this nation is directed. Pancasila as the conception of civil religion in Indonesia is a principle that can unite and guarantee social order. As a pluralistic country, we need glue that unites all kinds of differences while still acknowledging this diversity but upholding unity. In this study it was concluded that Pancasila with its precepts is a public moral value or civil religion in Indonesia which is able to provide strength for the continuity and glory of the life of the nation and state.